Frontispiece: Synthesis of Alternating Donor–Acceptor Ladder‐Type Molecules and Investigation of Their Multiple Charge‐Transfer Pathways. Issue 22 (22nd May 2018) - Cai, Zhengxu; Zhang, Na; Awais, Mohammad A.; Filatov, Alexander S.; Yu, Luping
Abstract : Molecular Electronics The synthesis as well as the optical and charge‐transport properties of a series of stable and soluble donor–acceptor ladder‐type heteroacenes with up to 24 fused rings are described in the Communication by L. Yu et al. on page 6442 ff.